Os programas de transferência de renda em países específicos da América Latina e no Brasil - Boyadjian, Ana Carolina Paes de Barros (2009)
The conditional cash transfers programs, indicated by World Bank as an expression of social politics to be carried by the State, have gained force in some countries in Latin America, especially in Brazil under the Lula s government, but not restricted on it. In the way where this social proposal action occurs, the diffusion of neoliberal ideas and the attempted destruction of social rights constructed and won in the post-war period, this dissertation aims to recover and examine the role of cash transfers in Latin America, specifically in Argentina, Chile, Mexico, Uruguay and Brazil. This dissertation specifically contemplates an introduced of the programs for conditional cash transfers in Brazil, included in government from 1990 to 2008, ie from Fernando Collor de Mello, of Fernando Henrique Cardoso and Luis Inacio Lula da Silva. Thus, before describing the situation and results in each government, resumes the discussion between welfare and rights , under the background of the new concept of poverty and new poverty . For the Bolsa Família, a program of income transfer that was not similar in the history of the country , it presents its main results, but calls attention to his limited action in that it is not complemented by actions and policies that modify or eliminate the factors determining the generation of structural poverty